Levels of macrophage inflammatory protein 1α-(MIP-1α) and MIP-1β in intervillous blood plasma samples from women with placental malaria and human immunodeficiency virus infection - Sujittra Chaisavaneeyakorn (2018)
Macrophage inflammatory protein-1α (MIP-1α) and MIP-1β play an important role in modulating immune responses. To understand their importance in immunity to placental malaria (PM) and in human immunodeficiency virus (HIV)-PM coinfection, we investigated levels of these chemokines in the placental intervillous blood plasma (IVB plasma) and cord blood plasma of HIV-negative PM-negative, HIV-negative PM-positive, HIV-positive PM-negative, and HIV-positive PM-positive women. Compared to HIV-negative PM-negative women, the MIP-1β concentration in IVB plasma was significantly elevated in HIV-negative PM-positive women and HIV-positive PM-positive women, but it was unaltered in HIV-positive PM-negative women. Also, PM-infected women, irrespective of their HIV status, had significantly higher levels of MIP-1β than HIV-positive PM-negative women. The MIP-1α level was not altered in association with either infection. The IVB plasma levels of MIP-1α and MIP-1β positively correlated with the cord blood plasma levels of these chemokines. As with IVB plasma, only cord plasma from PM-infected mothers had significantly elevated levels of MIP-1β compared to PM-negative mothers, irrespective of their HIV infection status. MIP-1β and MIP-1α levels in PM-positive women were positively associated with parasite density and malaria pigment levels. Regardless of HIV serostatus, the IVB MIP-1β level was significantly lower in women with PM-associated anemia. In summary, an elevated level of MIP-1β was associated with PM. HIV infection did not significantly alter these two chemokine levels in IVB plasma.